Chronic otitis media. Issue 4 (July 2015) - Wallis, Sebastian; Atkinson, Helen; Coatesworth, Andrew P
Abstract: Chronic otitis media (COM) is a common problem facing general practitioners, pediatricians and otolaryngologists. This article reviews the aetiopathogenesis, epidemiology, presentation, natural history, complications and management of COM. The literature was reviewed by using the PubMed search engine and entering a combination of terms including "COM", "diagnosis", "incidence", "complications" and "management". Relevant articles were identified and examined for content. What is the "take-home" message for the clinician? COM is a common problem with various sub-categories according to the disease state. It most commonly presents with painless otorrhoea and hearing loss. Treatment options vary according to the activity and type of disease encountered. COM carries significant patient morbidity.